2008
DOI: 10.1189/jlb.0808491
|View full text |Cite
|
Sign up to set email alerts
|

Differential lymphopenia-induced homeostatic proliferation for CD4+ and CD8+ T cells following septic injury

Abstract: Sepsis is a severe, life-threatening infection and a leading cause of death in hospitals. A hallmark of sepsis is the profound apoptosis-induced depletion of lymphocytes generating a lymphopenic environment. As lymphopenia can induce nonantigen-driven homeostatic proliferation (HP), we examined this process during sepsis. CD4(+) and CD8(+) T cells, which were depleted within 24 h of sepsis induction, remained at significantly reduced levels until Day 21 when normal numbers were detected. When HP was examined, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 37 publications
10
76
1
Order By: Relevance
“…The first study included nine patients with Staphylococcus aureus septic shock (26), and no specific T-cell repertoire modifications were observed. In the second study, Unsinger et al (27) showed that after cecal ligation and puncture, mice presented with lymphopenia but that the TCR repertoire measured 21 days after cecal ligation and puncture was not skewed toward any Vβ type but resembled the repertoire found in normal mice. The authors concluded that, after sepsis, T-cells were not primed to any antigen resulting from the infection.…”
Section: Discussionmentioning
confidence: 97%
“…The first study included nine patients with Staphylococcus aureus septic shock (26), and no specific T-cell repertoire modifications were observed. In the second study, Unsinger et al (27) showed that after cecal ligation and puncture, mice presented with lymphopenia but that the TCR repertoire measured 21 days after cecal ligation and puncture was not skewed toward any Vβ type but resembled the repertoire found in normal mice. The authors concluded that, after sepsis, T-cells were not primed to any antigen resulting from the infection.…”
Section: Discussionmentioning
confidence: 97%
“…Sepsis is known to cause acute thymic atrophy in the rodents which is associated with thymocyte apoptosis and characterized by a reduction in thymus size and weight caused by acute loss of immature DP cortical thymocytes [28–31]. Since mature CD4 + and CD8 + SP subsets arise from immature DP cells, decreased DP numbers at 20 h post-CLP would eventually result in reduced numbers of these mature subsets, as observed by Unsinger et al [32]. Thus, our data, showing a dramatic and acute DP-subset specific loss of T cells in the thymus after sepsis, is in accordance with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed decreased number of circulating lymphocytes predicting the bacterial origin of infection (AUC 0.841) is interesting because circulating lymphocytes are not frequently used by clinicians. The reason for the poorly estimated value of low lymphocyte numbers in bacterial infections could be that most authors describe lymphocytopenia in association with severe sepsis and septic shock [29].…”
Section: Discussionmentioning
confidence: 99%